Experiential education as a strategy to preserve Maqasid Al-Shariah by identifying and addressing stigmatic views held by pharmacy students of patients with substance use disorders - Mohd Taufek, Nor Hidayah; Halimi, Syafiqah Nadiah; Ab Rahman, Norny Syafinaz; Zin, Che Suraya; Che Mohamad, Che Anuar; Turner, Christopher John (IIUM Press, 2021)
Introduction: Stigmatising people with a history of substance use disorders (PHSUDs) is discriminatory, causes harm by hindering access to health services and promotes relapse. It jeopardises the preservation of Maqasid Al-Shariah, particularly the protection of life and well-being. Experiential education (EE) is a potential strategy to overcome stigma through direct experience with PHSUDs. This study aimed to identify stigmatised views of PHSUD's held by pharmacy students and, in accord with Maqasid Al-Shariah, the effectiveness of EE in changing those views. Materials and methods: Interviews were conducted with seven undergraduate pharmacy students who provided care to PHSUDs through an EE programme. A semi-structured interview guide was used to explore students' perceptions on stigma. Each interview was audio-taped, transcribed verbatim and translated into English. Data were manually sorted and coded using Microsoft Excel 2016 and subjected to thematic analysis. Results: The following themes related to stigma were identified: 1) individuals are to blame 2) moral versus biological views of addiction 3) stereotypes of unpredictability and dangerousness 4) lack of didactic education/training for pharmacy students regarding PHSUDs and 5) lack of face-to-face experiential education with PHSUDs. Less stigma and greater empathy towards PHSUDs were reported post-intervention attributable to increased knowledge about substance abuse and face-toface interactions with PHSUDs. Conclusion: Pharmacy students have pre-conceived stigmatic views regarding PHSUDs modifiable through experiential education. Contact by pharmacy students with stigmatised patients promotes health care without discrimination as advocated in the teaching of Islam. Future interventions to reduce stigma are required to preserve Maqasid Al-Shariah.